Caracterização do perfil imuno-hematológico das reações transfusionais tardias em pacientes com doença falciforme politransfundidos no Hemocentro do Amazonas - Santos, Lorena Alves (2023)
The most frequent late transfusion reactions are alloimmunization and hemolysis, observed in up to 70% of patients with sickle cell disease (SCD) who received multiple transfusions. The immunohematological profile of these reactions is characterized by the identification of alloimmunization, with or without the presence of hemolysis through tests such as a positive irregular antibody test, indicating a potentially hemolytic antibody specific for blood group systems such as Rh, Kell, Kidd, Duffy and MNS. Objective: To characterize the immunohematological profile of late transfusion reactions in patients with sickle cell disease who received multiple transfusions. Methodology: Prospective descriptive observational study of these patients, including children, adults and elderly people of both sexes undergoing chronic transfusion therapy. Patients with multiple transfusions exposed to three or more units of blood products during twelve months. Results and Discussion: 44 patients with multiple transfusions were included in the project, the majority of whom were female (54.5%), adults (40.9%) and type O (61.3%) of the ABO system. Regarding the phenotyping of blood group systems, the most significant results from a transfusion point of view were found in the Rh system, a frequency of 26.6% of the RZRZ phenotype (CDE/CDE), a patient with the RHD variant presenting anti-RhD and a patient with RHCE variant (R1 wR1) presenting anti-e l and anti-E. As for the Kell system, 61.3% presented K-k+, with considerable difficulty in finding compatible blood donors in these cases. Among the patients included, 20.4% presented one or more alloantibodies, showing late alloimmunization reactions, 9% presented autoantibodies, suggesting a possible late immunomodulation reaction. Regarding the verification of post-transfusion hematological tests, 31.8% of patients presented laboratory indicators of post-transfusion Hemolysis with the result of altered DHL and 54.5% presented a very low increase in hemoglobin after blood transfusions, suggesting possible delayed hemolytic reactions. Conclusion: The results of this study demonstrate the characterization of the immuno-hematological profile of late alloimmunization and hemolytic transfusion reactions in patients with Sickle Cell Disease who received multiple transfusions treated at the Hematology and Hemotherapy foundation from Amazonas, constituting unprecedented data obtained during clinical-laboratory follow-up up to 28 days after transfusions